Analisis Cost-Volume-Profit (CVP) sebagai Dasar Pengambilan Keputusan pada UMKM toko baju z.nl di Platform Shopee: Cost-Volume-Profit (CVP) Analysis as a Decision Basis for MSMEs in z.nl clothing stores on the Shopee Platform - Zinedin Ridwan Rojak; Muhammad Khoiro Nazed; Achmad Nauval Pratama; Anggi Cahya Maulana; Farhan Abdillah Fauzi Suhara (PT Cakrawarti Empat Proksi, 2026)
The development of digitalization encourages fashion MSMEs to utilize e-commerce platforms such as Shopee as a medium for marketing and selling products. However, high administrative costs, promotional expenses, and intense price competition create challenges for businesses in achieving optimal profits. This study aims to analyze the implementation of Cost-Volume-Profit (CVP) analysis as a basis for decision-making in the z.nl clothing MSME on the Shopee platform. The research method used is a quantitative descriptive method with a case study approach. Data were collected through observation, interviews, and documentation related to fixed costs, variable costs, sales volume, and business profits. CVP analysis was conducted by calculating contribution margin, break even point (BEP), margin of safety (MOS), and target profit(Negeri et al., 2023). The results indicate that the implementation of CVP analysis assists MSMEs in determining the minimum sales level, estimating expected profits, and supporting decision-making related to selling prices, cost efficiency, and sales strategies. Therefore, CVP analysis can be used as an effective profit planning tool to improve the sustainability and competitiveness of fashion MSMEs in the digital era.